Wirausaha Abon Ikan Tuna : Peningkatan Pendapatan Disabilitas Kota Bengkulu - Barika, Barika; Dewi Anggraini, Eka; Izharudin (Kreativasi : Journal of Community Empowerment, 2023)
Tuna is a marine product that is mostly produced by fishermen in the city of Bengkulu at a relatively affordable price. The training activities for making shredded tuna business generally aim as a source of fulfilling nutrition, the nutrients contained in tuna fish are able to meet the nutritional needs of families in the disabled group. In addition to fulfilling family nutrition, the processing of shredded tuna produced will be able to become a source of income for people with disabilities. This community service activity is carried out using counseling methods and training in making shredded tuna. From the activities carried out it can be seen that the participants were enthusiastic to take part in the activities both in the delivery of material and practice from people with disabilities in Bengkulu City.